A framework for a responsible circular economy. (10th May 2023) - Purvis, Ben; Celebi, Dilay; Pansera, Mario
Abstract: The move towards a Circular Economy (CE) from the perspective of a 'just transition' necessitates an approach which deems stakeholder knowledge and agency as central. Under this paradigm the transition to a CE is conceived not as a technocratic challenge, but as a process of socioeconomic transformation grounded in principles of social and environmental justice. We suggest that Responsible Research and Innovation (RRI), as an approach for considering the relation of science to wider society, in particular the constituent concepts of anticipation, inclusion, reflection, and responsiveness (Owen et al., 2013), presents itself as a lens through which we can embed considerations of justice within CE practices. In exploring these dimensions with a critical view to how the CE discourse has often failed to consider who will benefit from the transition to a CE, we present a framework for supporting the design of responsible CE practices. We argue that such a framework can provide a starting point for future refinement and enrichment of the decision context faced by the relevant groups in the course of the transition to a just CE.